The use of repetitive transcranial magnetic stimulation (rTMS) following traumatic brain injury (TBI): A scoping review. Issue 3 (16th March 2021) - Pink, Aimee E.; Williams, Claire; Alderman, Nick; Stoffels, Martine
ABSTRACT: There is continued interest in developing effective and innovative treatment approaches to manage and improve outcomes after traumatic brain injury (TBI). Included in this, is the potential use of repetitive transcranial magnetic stimulation (rTMS), a neuromodulatory tool currently recommended by the National Institute for Health and Care Excellence as a treatment for depression. This review considers the application of rTMS after TBI, focussing on its therapeutic efficacy for a broad range of sequalae, whether an optimal and safe rTMS protocol can be determined, and recommendations for future clinical and research work. Five research databases (MEDLINE, CINAHL, PsychINFO, SCOPUS, and Web of Science) were electronically searched, identifying 30 empirical studies (single and multiple subject case reports; randomized controlled trials) for the full review. Evidence suggests that rTMS has the potential to be an efficacious therapeutic intervention for multiple symptoms after TBI, including depression, dizziness, central pain, and visual neglect. However, the picture is less encouraging for prolonged disorders of consciousness and mixed for cognitive outcomes. Overall, rTMS was well-tolerated by patients, although some incidents of side effects and seizures have been reported. Recommendations are made for more comprehensive guidelines and sufficient reporting of rTMS parameters and procedures.